Asymmetric Price Transmission in Indonesia's Wheat Flour Market - Gonzalo J. Varela; Kiyoshi Taniguchi (Asian Development Bank (ADB), 2014)
Data indicate that its domestic price in Indonesia has been increasing regardless of movements in the international price of wheat. A test for asymmetric price transmission from international wheat to domestic wheat flour markets is conducted using an error correction model and find the presence of asymmetric price transmission. The upward adjustment in the domestic price of wheat flour is much faster than its adjustment downward when it deviates from long-run equilibrium. Our results are robust to use of disaggregated data as well as to inclusion of additional of control variables such as prices of other inputs. We argue that asymmetric transmission occurs due to market concentration of wheat flour milling. We offer some policy suggestions for correcting these.
hdl:11540/1975
Keywords: F12; L11; Q11; Q13; Q17; 330; spatial integration; asymmetric price transmission; monopolistic competition; commodity prices; agricultural market; wheat flour